Increasing N Retention in Coastal Plain Agricultural Watersheds - Kenneth W. Staver (The Scientific World Journal)
Historically, N availability has limited agricultural production as well as primary production in coastal waters. Prior to the middle of the last century, N available for grain production generally was limited to that supplied by previous legume crops, released from soil organic matter, or returned to the soil in animal wastes. The development of infrastructure to produce relatively low-cost inorganic N fertilizers eliminated the need to focus management of the entire agricultural system on increasing soil N availability. Increased N availability has contributed to dramatic increases in agricultural production but also has led to increased losses of both N and C from agricultural systems. N losses from cropland have been linked to increased algal production in the Chesapeake Bay, with N loss from cropland estimated to be the primary N input to the Bay from Coastal Plain regions of the watershed. The decade-long effort to reduce these losses has focused on reducing agricultural N use, but this strategy has yet to yield apparent reductions in N loadings to Coastal Plain tributaries. Although nitrate leaching losses are often attributed to inefficient use of N inputs, soil nitrate data indicate that both corn and soybeans can utilize nearly all available soil nitrate during periods of active growth. However, both crops tend to stop utilizing nitrate before mineralization has ceased, resulting in a late season buildup of root zone nitrate levels and significant leaching losses even when no N was applied. Reducing nitrate losses due to the inherent N inefficiency of summer annual grain crops will require the addition of winter annual crops to rotations or changes in weed management approaches that result in plant N uptake capacity being more closely matched to soil microbial N processes.